Defrosting dynamic behaviors of a propane air conditioner and its rotary compressor under low ambient temperature conditions. (December 2021) - Du, Yanjun; Wu, Jianhua; Lin, Jie; Wang, Che; Chen, Rui; Li, Jinbo
Abstract: Due to the great potential of propane in environmental protection and thermodynamic properties, the promotion of propane room air conditioner will make a great contribution to environmental protection. The defrosting behaviors of propane room air conditioner system and rotary compressor were studied by experiments in this paper. Experimental analysis redefines and distinguishes defrosting time and frost melting time, and their relationship with condition temperature is different. The experimental results show that the lower the ambient temperature was, the longer the defrosting time was, but the shorter the frost melting time on the outdoor heat exchanger was. The state of the oil sump and foam layer in propane rotary compressor using Mineral Oil (MO) was recorded and the variation reason for liquid level was analysed during defrosting. Combined with the change of viscosity and liquid level of the oil sump, the experimental results show that the compressor has abnormal oil discharged, and the lower the ambient temperature was, the larger the oil discharge was under three conditions during defrosting process. The total mass of the mixture in the oil sump under the three working conditions is 275.18 g, 289.10 g and 276.41 g, the lubricating oil is 202.97 g, 200.23 g and 189.71 g, and the refrigerant mass is 72.21 g, 88.87 g and 86.71 g respectively when the defrosting process ended. This study will provide an experimental basis of the reliability study and application of propane air conditioners.